2000
DOI: 10.1021/om000391q
|View full text |Cite
|
Sign up to set email alerts
|

Observation of New Intermediates in the Reaction of Dihydrogen with Iridium, Rhodium, and Mixed Metal A-Frame Complexes with Parahydrogen-Induced Polarization

Abstract: The reaction of hydrogen with iridium and rhodium µ-S A-frame complexes has been investigated using parahydrogen-induced polarization (PHIP) NMR spectroscopy. The reaction of Ir 2 (µ-S)(CO) 2 (dppm) 2 where dppm ) bis(diphenylphosphino)methane with hydrogen proceeds by two addition pathways corresponding to oxidative addition inside (endo) and outside (exo) the pocket of the A-frame complex. The exo addition pathway yields a kinetically significant dihydride that has not been previously reported. This species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The study of the characteristic line shape caused by the interaction of dissolved p-H 2 with the catalyst [1,4bis(diphenylphosphino)butane](1,5-cyclooctadiene)rhodium(I) tetrafluoroborate was performed in acetoned 6 . Parahydrogen enriched hydrogen gas is prepared at 77 K with about 50% of p-H 2 spin-isomer.…”
Section: Samples and Compoundsmentioning
confidence: 99%
“…The study of the characteristic line shape caused by the interaction of dissolved p-H 2 with the catalyst [1,4bis(diphenylphosphino)butane](1,5-cyclooctadiene)rhodium(I) tetrafluoroborate was performed in acetoned 6 . Parahydrogen enriched hydrogen gas is prepared at 77 K with about 50% of p-H 2 spin-isomer.…”
Section: Samples and Compoundsmentioning
confidence: 99%
“…(11) The coherent evolution of the density operator under the influence of the Hamiltonian is governed by the following equation of motion (12) In this equation we have followed the NMR convention and set the constant ћ = 1, which is equivalent to measuring energies in angular frequency units. Since the Hamilton operator does not explicitly depend on time, the equation of motion of the density matrix can be solved with the help of the following unitary propagator (13) The time dependent density matrix is (14) Using r ˆ(t) the expectation value of any physical observable <Â> is given as: (15) In the case of conversion of para-ice to ortho-ice we are interested in the relative amount of molecule pairs which are still both in the para-state or which both are in the ortho-state after time t. These numbers are proportional to the expectation values of the matrices ( 16) and (17) Inserting the time dependent density matrix [14] gives (18) and (19) For the further discussion it is very useful to employ a base set where the Hamiltonian Eq. 10 is diagonal.…”
Section: Theorymentioning
confidence: 99%
“…The mechanisms of the ortho/para conversion of hydrogen have been the topic of various experimental and theoretical studies. This interest in the conversion was triggered by three main reasons, namely (i) the application of combined studies of the ortho/para spin conversion of dihydrogen and of the hydrogen/deuterium scrambling reactions as tools for the elucidation of the mechanisms of catalytic hydrogenation reactions; 3,4 (ii) the application of para-hydrogen as an agent for the sensitivity enhancement of liquid state NMR, [5][6][7] in particular for studies of catalysis; and (iii) the quantum mechanical nature of the ortho-and para-states, which is interesting by itself; (iv) the usage of ortho/para-water ratios as remote sensors for the thermal history of the ice core of comets; 8-11 (v) to understand the mechanisms of the conversion of para-formaldehyde to ortho-formaldehyde by surface adsorption. 12 The studies of dihydrogen metal complexes started when Wilkinson found the first catalysts which are able to take up and easily activate molecular dihydrogen during the hydrogenation of double bonds.…”
Section: Introductionmentioning
confidence: 99%